Working Creatively with Stories and Learning Experiences Engaging with Queerly Identifying Tertiary Students - Crowhurst, Michael (Creativity, Education and the Arts, 2018)
'This book is a thorough original compilation of how to work with stories, why we work with stories, and provides much scope and opening for the reader to take the ideas and strategies into their own fields of research and learning. This is a very useful guide not only in support of LGBTIQ issues but also a very accessible academic overview of using, analyzing and creatively engaging with narratives in many disciplines, with many communities, and in multiple settings.' -Maria Pallotta Chiarolli, Deakin University, Australia Stories are a valuable vehicle for practitioners in research, education, human services and the arts to enable individual and cultural change. The authors describe and deploy a variety of methods that can be used by teachers, researchers, artists, youth and community workers, and other professionals to analyse stories in ways that can promote learning and wellbeing and enhance professional practice. Offering a concise and user-friendly assemblage of techniques on how to creatively engage with stories, the authors explore and exemplify these techniques through the narratives of Queerly Identifying Tertiary Students. This practical and innovative volume will appeal to readers, researchers and practitioners alike. Michael Crowhurst is Lecturer in Education at RMIT University, Australia. Michael Emslie is Lecturer in Youth Work at RMIT University, Australia. .